1998
DOI: 10.1007/s004210050413
|View full text |Cite
|
Sign up to set email alerts
|

The effects of creatine supplementation on high-intensity exercise performance in elite performers

Abstract: The aim of this research was to determine whether creatine supplementation at a dose of 20 g x day(-1), given in 4 x 6-g doses (5 g creatine monohydrate and 1 g glucose) for 5 days, was effective in improving kayak ergometer performances of different durations. Sixteen male subjects with the following characteristics [mean (SEM)]: age 21 (1.2) years, height 170.2 (1.7) cm, weight 75.3 (2.3) kg, sigma8 skinfolds 59.3 (2.6) mm, and maximal oxygen consumption 67.1 +/- (4.3) ml x kg x min(-1), undertook three maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 24 publications
(34 reference statements)
2
24
3
1
Order By: Relevance
“…Possibly, the differences in total muscles mass involved during kayaking compared to wheelchair racing seemed to be of higher impact than expected and might be responsible for the reported discrepancies concerning an ergogenic effect. Moreover, lactate concentrations were not influenced by creatine supplementation in the present study, which supports the hypothesis that the glycolytic pathways were unaltered by creatine supplementation as proposed by Birch et al 2 Many studies in the past reported positive effects on performance of different types and durations after a short-term creatine supplementation, [1][2][3][4][5][6][7][8]21 whereas others found no effect. 16,[22][23][24][25][26] Interestingly, in most of the studies showing no ergogenic effect on exercise performance after creatine supplementation, a time or distance trial was performed, [22][23][24][25][26] whereas in studies with a positive effect the time to exhaustion at a given workload was determined.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Possibly, the differences in total muscles mass involved during kayaking compared to wheelchair racing seemed to be of higher impact than expected and might be responsible for the reported discrepancies concerning an ergogenic effect. Moreover, lactate concentrations were not influenced by creatine supplementation in the present study, which supports the hypothesis that the glycolytic pathways were unaltered by creatine supplementation as proposed by Birch et al 2 Many studies in the past reported positive effects on performance of different types and durations after a short-term creatine supplementation, [1][2][3][4][5][6][7][8]21 whereas others found no effect. 16,[22][23][24][25][26] Interestingly, in most of the studies showing no ergogenic effect on exercise performance after creatine supplementation, a time or distance trial was performed, [22][23][24][25][26] whereas in studies with a positive effect the time to exhaustion at a given workload was determined.…”
Section: Discussionsupporting
confidence: 90%
“…Further, creatine supplementation enhanced exercise performance in elite kayak paddlers during time trials between 90 and 300 s duration. 7 As during the propulsion of a wheelchair, less but similar muscle groups are involved as during kayaking, a positive ergogenic effect of a creatine supplementation was also expected during an all-out 800 m wheelchair test, a hypothesis that was not confirmed by our study. Possibly, the differences in total muscles mass involved during kayaking compared to wheelchair racing seemed to be of higher impact than expected and might be responsible for the reported discrepancies concerning an ergogenic effect.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Current research has shown that ingesting sodium bicarbonate may enhance aspects of sprint performance such as power output, total anaerobic work, and delaying fatigue (7,8,32,38,39,40,41,42,65). Lavender and Bird (1989), and Bishop et al (2004Bishop et al ( -2005, concluded that sodium bicarbonate supplementation improved power output levels in repeated sprints.…”
Section: Statement Of the Problemmentioning
confidence: 99%